SOURCE WISE INCIDENCE OF MALARIA IN SUB-UNITS OF AURANGABAD, INDIA - SHAIKH, J. D.; POKALE, S. S.; NIKAM, S. R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2002)
The source wise blood smear collection and examination of (positive) malaria from the various sub units of Aurangabad during 1999-2000 and 2000-2001 showed the percentage of total positive from active blood smears collected and examined was 0.5699% and 1.073%.